Board diversity and firm value; mediating effect of CSR of listed oil firms in Nigeria - Chondough, Stephanie M. (Applied Studies in Agribusiness and Commerce, 2021)
In this empirical study, the mediating effect of corporate social responsibility (CSR) on the nexus between corporate value and board diversity is investigated. However, hypotheses developed for this study were tested with annualized panel dataset of eight (8) Nigerian listed oil and gas firms in the upstream sector spanning 2012 to 2019. Stakeholder theory was used to underpin the study. The study employed three indicators for board diversity (board professionalism, board nationality and board gender), Tobin’s Q and amount spent on CSR. The panel regression results show that looking at the indirect effect in Model One; board diversity has no significant effect on firm value. However, empirical findings indicated that CSR exerts a significant and positive relationship with corporate value. Considering Model Two, the results show that CSR plays a pertinent role in establishing the nexus between corporate value and board diversity, this finding is congruent with stakeholder theory. The study recommends that environmental sensitive firms should maintain an appropriate and balance diverse board as it plays a pertinent and significant role in establishing the nexus between stakeholder relationship and the firms, which can also serve as a mechanism to mitigate manager's opportunistic tendencies behind CSR investment.JEL code: L95, M14, M41